A Feasibility Study on a Micro Hydro Power Plant at Coban Jahe Waterfall, Jabung, Malang Regency - Sudarman Sudarman; Wahyu Guszolil; Daryono Daryono; Muhammad Lukman (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering), 2021)
Micro Hydro Power (MHP) Plant is a small-scale power plant under 100 kW. Generally, MHP is built in a place that the electricity network has not touched. Many waterfalls in Taji Village are only used as tourist attractions. One of them is Coban Jahe waterfall which has a water discharge of 0.60567 m3/s in the dry season. Waterfall in Coban Jahe was used and planned as Micro Hydro Power Plant, it was called as MHP. Potential electric power generated from the MHP Coban Jahe Waterfall is 14.0368 kW with an effective head of 3.4742 m. The results show from the financial analysis, the construction of MHP is quite feasible with NPV of Rp. 45,676,769, BCR of 1.0852, which means it is feasible to be continued, the Payback Period is 9 years which does not exceed the project life, and the IRR obtained is 10,0087% which the projects are feasible and profitable to build.